Prevalence of Overlap Syndrome. Obstructive Sleep Apnea in Patients with Chronic Obstructive Pulmonary Disease. A study protocol. - Oliveira, Julio Cesar Mendes; Silva, Anderson Soares; Beloto, Ana Carolina Negrinho de Oliveira; Urbano, Jéssica Julioti; Oliveira, Ezequiel Fernandes; Perez, Eduardo Araujo; Peixoto, Roger Andre Oliveira; Santos, Israel Reis; Oliveira, Luis Vicente Franco (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: Chronic obstructive pulmonary disease (COPD) and Obstructive sleep apnea (OSA) cause an inflammatory response and hypoxia. Patients who have both conditions have increased morbidity and mortality. Overlap syndrome between OSA and COPD is important but under-recognised. Objectives: We aimed to determine the prevalence and severity of overlap syndrome in patients with COPD through the overnight standard polysomnography. Methods/Design: A consecutive single-center cross-sectional study will be performed. The design, conduct and report of this study followed the guidelines of the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) statement. The sample will be of convenience, recruited consecutively with respiratory complaints that seek care in a private clinic specializing in pulmonology in the city of Cascavel, in the state of Paraná, from September 2016 to July 2017. All subjects will be submitted to the same evaluation protocol described subsequently. Initially will be collected data on baseline demographic, anthropometric and clinical aspects, including body mass index, neck, hip and waist circumferences, respiratory and cardiac rates, peripheral blood pressure, and BODE index. After this phase of the study, patients will perform lung function tests through petismography, sleep studies using the standard overnight PSG, and respond to the Berlin and Pittsburgh questionnaires, and Epworth Sleepiness Scale.